Fatty acid composition and cholesterol content of the fat of pigs of various genotypes - Csapó, János; Vargáné Visi, Éva; Csapóné Kiss, Zsuzsanna; Csokona, Éva (Acta Agraria Kaposváriensis, 2002)
The authors determined the fatty acid composition and the fat cholesterol content of the fat of Mangalica, Hungarian Large WhitexHungarian Landrace and Mangalica x Duroc pigs. It was established that no significant difference among the three genotypes could be detected with respect to saturated, unsaturated, or the essential fatty acids, nor in regard to cholesterol content. The findings of these investigations indicate that in the three pig genotypes studied fat cholesterol content varies between 71 and 109 mg/100 g. Attention is also drawn to the high oleic acid content (relative% age 43.57–44.81) and linoleic acid content (relative % age 10.63–11.47) of pig fat.